Implementación de las TIC en la enseñanza de la física, factibilidad y eficacia en nuestro país - Osorio Meneses, Jhon Raul; Prieto Murcia, Miguel Antonio; Infante Luna, Esperanza Del Pilar (Revista Científica, 2011)
For some decades they have come incorporating the Technologies from the Information and the Communication (TICs) to complement the educative material, and so a fort was expected as much impact in the methods of education revolutionizing therefore the education student as university. (Eduteka, 2007) From the sprouting of the Web and its use in education an educative transformation in developed countries and in the countries of the Third World was even speculated on (Eduteka, 2007); despite some authors the educative level of the Latin American school and the school in Member States of theOrganization for the Economic Cooperation and the Development speak of an increase inthe breach between. With the purpose of in particular to make an evaluation of theimplementation of the TICs in education and in education of the physics in Colombia,information reported by different authors in relation to the subject was compiled, whichwas systematized and analyzed. In this article the results of this analysis appear and fromthese some aspects associated with the effectiveness and the feasibility of the use of theTics in our country consider, which can as much be considered by investigators as byusers of these technologies.